Face Management and Negative Strengthening: The Role of Power Relations, Social Distance, and Gender - Gotzner, Nicole; Mazzarella, Diana (Frontiers in Psychology, 2021)
Negated gradable adjectives often convey an interpretation that is stronger than their literal meaning, which is referred to as ‘negative strengthening’. For example, a sentence like ‘John is not kind’ may give rise to the inference that John is rather mean. Crucially, negation is more likely to be pragmatically strengthened in the case of positive adjectives (‘not kind’ to mean rather mean) than negative adjectives (‘not mean’ to mean rather kind). A classical explanation of this polarity asymmetry is based on politeness, specifically on the potential face threat of bare negative adjectives (Horn, 1989, Brown & Levinson, 1987). This paper presents the results of two experiments investigating the role of face management in negative strengthening. We show that negative strengthening of positive and negative adjectives interacts differently with the social variables of power, social distance, and gender.